4(3x-6)=6x-2

Simple and best practice solution for 4(3x-6)=6x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-6)=6x-2 equation:



4(3x-6)=6x-2
We move all terms to the left:
4(3x-6)-(6x-2)=0
We multiply parentheses
12x-(6x-2)-24=0
We get rid of parentheses
12x-6x+2-24=0
We add all the numbers together, and all the variables
6x-22=0
We move all terms containing x to the left, all other terms to the right
6x=22
x=22/6
x=3+2/3

You can always share this solution

See similar equations:

| .66x=-12 | | 19+b=5.7 | | -30+2y=56 | | 2-+4n=-5-3n | | 2+10x=-34-x | | 2+10x=34-x | | 4w-12=-48 | | 4*3^x+1-9^x=27 | | -2(x-6)=14 | | 4*3^x+1-9x=27 | | 9x-1633x=20 | | -3x^2+3-8x=0 | | (x+9)2=9 | | 23=5-t | | ?2(3x?4)?x?3=33 | | t2-7t-8=0 | | 4(2x+1)-2x=-8 | | 0.25x+0.20(100-x)=21 | | 5-8x=12-7x | | H(t)=14+32t-16^2 | | 0.08(x+3000)=3840 | | x^+3x=70 | | (12x-53)+(6x+25)=180 | | 5(3x-3)=16 | | X^3+10x^2+24x-92=0 | | 2x=5×-30 | | 5x+12=9x+48 | | 6x36=72 | | 24-6x+32-4x=180 | | A=(15+x) | | 3(a+4)=6(a+2)-3a | | x+2x=192 |

Equations solver categories